Application of Fractional Factorial Design (FFD) for Screening of Significant Factor in Influencing Succinic acid Production from Biodiesel Based Glycerol Using Escherichia Coli - Mimi Sakinah, A. M.; Noor Suhana, Adzahar (2011)
The production of succinic acid from biodiesel based glycerol was carried out using Escherichia coli K12 MG1655 strain. The contribution of every parameter was evaluated and optimized using statistical modeling. A 2 6-1 fractional factorial design (FFD) was applied to screen the effect of substrate concentration, tryptone concentration, sodium carbonate concentration, inoculums density, pH and incubation period for Escherichia coli reaction on succinic acid production. The result of first order factorial design showed that glycerol concentration, tryptone concentration, incubation period and pH had significant positive effect (p>0.001) to the reaction. Meanwhile, inoculums density and Na2CO concentration exhibited insignificant effect in the reaction. In addition, interaction between inoculums density of substrate concentration and tryptone concentration, glycerol concentration and Na23CO concentration, tryptone concentration and pH, Na32CO concentration and incubation period and inoculums density with pH gave significant effects (p<0.001) to succinic acid production.